Outcomes in patients treated with chimeric antigen receptor T-cell therapy who were admitted to intensive care (CARTTAS): an international, multicentre, observational cohort study. Issue 5 (May 2021) - Azoulay, Élie; Castro, Pedro; Maamar, Adel; Metaxa, Victoria; de Moraes, Alice Gallo; Voigt, Louis; Wallet, Florent; Klouche, Kada; Picard, Muriel; Moreau, Anne-Sophie; Van De Louw, Andry; Seguin, Amélie; et al.
Summary: Background: Chimeric antigen receptor (CAR) T-cell therapy can induce side-effects such as cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome (ICANS), which often require intensive care unit admission. The aim of this study was to describe management of critically ill CAR T-cell recipients in intensive care. Methods: This international, multicentre, observational cohort study was done in 21 intensive care units in France, Spain, the USA, the UK, Russia, Canada, Germany, and Austria. Eligible patients were aged 18 years or older; had received CAR T-cell therapy in the past 30 days; and had been admitted to intensive care for any reason. Investigators retrospectively included patients admitted between Feb 1, 2018, and Feb 1, 2019, and prospectively included patients admitted between March 1, 2019, and Feb 1, 2020. Demographic, clinical, laboratory, treatment, and outcome data were extracted from medical records. The primary endpoint was 90-day mortality. Factors associated with mortality were identified using a Cox proportional hazard model. Findings: 942 patients received CAR T-cell therapy, of whom 258 (27%) required admission to intensive care and 241 (26%) were included in the analysis. Admission to intensive care was needed within median 4·5 days (IQR 2·0–7·0) of CAR T-cell infusion. 90-day mortality was 22·4% (95% CI 17·1–27·7; 54 deaths). At initial evaluation on admission, isolated cytokine release syndrome was identified in 101 patients (42%), cytokine release syndrome and ICANS in 93 (39%), and isolated ICANS in seven (3%) patients. Grade 3–4 cytokine release syndrome within 1 day of admission to intensive care was found in 50 (25%) of 200 patients and grade 3–4 ICANS in 38 (35%) of 108 patients. Bacterial infection developed in 30 (12%) patients. Life-saving treatments were used in 75 (31%) patients within 24 h of admission to intensive care, primarily vasoactive drugs in 65 (27%) patients. Factors independently associated with 90-day mortality by multivariable analysis were frailty (hazard ratio 2·51 [95% CI 1·37–4·57]), bacterial infection (2·12 [1·11–4·08]), and lifesaving therapy within 24 h of admission (1·80 [1·05–3·10]). Interpretation: Critical care management is an integral part of CAR T-cell therapy and should be standardised. Studies to improve infection prevention and treatment in these high-risk patients are warranted. Funding: Groupe de Recherche Respiratoire en Réanimation Onco-Hématologique.